Outlooks on Epstein-Barr virus associated gastric cancer. (May 2018) - Naseem, Madiha; Barzi, Afsaneh; Brezden-Masley, Christine; Puccini, Alberto; Berger, Martin D.; Tokunaga, Ryuma; Battaglin, Francesca; Soni, Shivani; McSkane, Michelle; Zhang, Wu; Lenz, Heinz-Josef
Highlights: Approximately 10% of all gastric cancers are related to EBV infection. EBV associated gastric cancers have a distinct molecular and clinical profile. These tumors have higher PD-L1 expression, PIK3CA mutations and hypermethylation. The role of immunotherapy in EBV associated gastric cancer is under investigation. EBV is a promising biomarker in gastric cancer. Abstract: Epstein-Barr virus associated gastric cancer (EBVaGC) comprises approximately 10% of gastric carcinomas. Multiple factors contribute to tumorigenesis, including EBV driven hypermethylation of tumor suppressor genes, inflammatory changes in gastric mucosa, host immune evasion by EBV and changes in cell cycle pathways. The unique molecular characteristics of EBVaGC, such as programmed death ligand 1 (PD-L1) overexpression, highlight the potential for using EBV as a biomarker for response to immunotherapy. Few studies have reported benefit from immunotherapy in EBV positive cancers, and clinical trials investigating the impact of checkpoint inhibitors in EBVaGC are currently underway. This review provides the most recent updates on molecular pathophysiology, epidemiology, clinical features and treatment advances pertaining to EBVaGC.